Entomological Risk Assessment for Dengue Virus Transmission during 2016–2020 in Kamphaeng Phet, Thailand - Thanyalak Fansiri; Darunee Buddhari; Nattaphol Pathawong; Arissara Pongsiri; Chonticha Klungthong; Sopon Iamsirithaworn; Anthony R. Jones; Stefan Fernandez; Anon Srikiatkhachorn; Alan L. Rothman; Kathryn B. Anderson; Stephen J. Thomas; et al. (Pathogens, 2021)
females. The majority of the 13,228 water containers examined were made from plastic and clay, with used tires serving as a primary container, with 59.55% larval abundance. Larval indices, as indicators of dengue epidemics and to evaluate disease and vector control approaches, were calculated. As a result, high values of larval indices indicated the considerably high risk of dengue transmission in these communities.
Keywords: Mosquito-borne diseases and control; Dengue and Mosquito Control Research; Viral Infections and Vectors